the Pengenalan Makanan Bernutrisi dan Pemeriksaan Saturasi Oksigen Pada Anak Penyandang Talasemia - Santi Nurul Kamilah Kamilah; Choirul Muslim; Fatimatuzzahra; Vestidhia Yunisya Atmaja; Dian Fita Lestari; Sipriyadi; Risky Hadi Wibowo (Cv. Utility Project Solution, 2023)
The majority of thalassemia patients in Rejang Lebong Bengkulu had dietary issues. Due to their parents' insufficient understanding of thalassemia, some of them do not undergo routine blood transfusions. With the goal to improve parents' understanding of thalassemia and its problems, this community service project was carried out at the Indonesian Thalassemia Parents Association (POPTI) organization in the Rejang Lebong Regency of Bengkulu. It included measuring oxygen saturation and introducing nutritious foods for people with thalassemia. In order to explain thalassemia, the inheritance of thalassemia features, and the introduction of significant nutritious foods for persons with thalassemia, this activity was carried out utilizing the telling method. On 10 thalassemia patients with ages ranging from 2 to 20 years old, the oxygen saturation was assessed using the direct survey method and an oximeter. According to the oximeter, all individuals with thalassemia have normal oxygen saturation levels. Both parents and kids are aware of the value of blood transfusions and a healthy diet for thalassemia. This activity has a good impact on parents and kids to improve parents' knowledge about thalassemia and its issues, the causes of thalassemia and its heredity, children's oxygen saturation, and its meaning. Parents may reduce the risk of health issues in people with halassemia by understanding the reasons for food that needs to be taken and needs to be avoided. Sebagian besar anak penyandang talasemia yang ada di Rejang Lebong Bengkulu mengalami permasalahan gizi. Beberapa diantaranya tidak melakukan transfusi darah rutin akibat pemahaman orang tua yang masih rendah mengenai talasemia. Kegiatan pengabdian kepada masyarakat ini dilakukan pada komunitas Persatuan Orang Tua Penderita Thalassemia Indonesia (POPTI) cabang Bengkulu yang ada di wilayah Kabupaten Rejang Lebong Bengkulu dengan tujuan untuk meningkatkan pemahaman orang tua tentang penyakit talasemia dan permasalahannya melalui pemeriksaan saturasi oksigen dan pengenalan makanan bernutrisi bagi penyandang talasemia. Kegiatan ini dilaksanakan dengan metode ceramah untuk menyampaikan penjelasan tentang talasemia, pewarisan sifat talasemia, pengenalan makanan bernutrisi penting bagi penyandang talasemia. Pemeriksaan saturasi oksigen dilakukan dengan metode survei langsung menggunakan alat oximeter pada 10 penyandang talasemia dengan rentang usia 2-20 tahun. Oximeter menunjukkan bahwa, semua penyandang talasemia memiliki saturasi oksigen dalam kadar normal. Orang tua dan anak telah memahami pentingnya transfusi darah dan makanan bernutrisi yang tepat bagi talasemia. Kegiatan ini telah memberikan manfaat yang baik bagi orang tua dan anak dalam upaya peningkatan wawasan dan pemahaman orang tua tentang penyakit talasemia dan permasalahannya, penyebab munculnya talasemia dan pewarisannya, saturasi oksigen anak serta maknanya. Orang tua dapat memahami alasan suatu makanan perlu dikonsumsi dan perlu dihindari bagi anak penyandang talasemia sehingga dapat mengurangi kemungkinan permasalahan kesehatan yang muncul pada anak penyandang talasemia.